Hemipterologisches aus Spanien. - Bator, Adelheid (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The above publication deals with the results of explorations of biotops near to the ground from the environment of Madrid, enumerating the material collected, 71 genera (90 species). The Lygaeidae are seen to be most numerously represented. Only a small part of the species belongs to the palaearctic type of distribution, while some of them must be regarded as mediterranean species. A few records of Heteroptera in this paper may be new.